The Holy Quran According to Islamic Belief - Gafarov, Alirza (Scholarya Demo Journal of Ruby, 2019)
Man aspires to determine his goals and target instictively. Searching the answers to the questions about birth and the purpose of life, humans found some of the answers of their questions, however, they could fill the gaps with God and religion. Through revelations Islam was directing people and giving them new targets. There are various ways of acquiring knowledge. One of the most important of these ways is wahy (revelation). From this point of view, the Quran can be considered a divine book that helps people to find their place in life. The Quran, sent down by divine inspiration from God, is not merely a matter of religion, but also a number of issues related to the morality, law, and history that humans have forgotten. The Quran is attractive both in terms of its style and the topics it covers in the modern era. At the same time, it is accepted as amiracle in Islamic thought for its uniqeness. The article gives a brief summary of the essence of revelation, the emergence of the Quran and its comprehension and gives some examples to explain the subject.